A Two-Fold Approach in Investigating the Factors in Practice Teaching Experiences of Technology Livelihood and Vocational Education Preservice Teachers - Hericco, De Los Nieves; Ian, Galino Egar; Adam, Sarucam; Tadashi, Senobio John; Ian S., Somosot (Journal of Technical Education and Training, 2023)
Pre-service teacher preparation programs vary greatly across countries. The most important part of a teacher training program is pre-service teaching regarded as the element of teacher training that is most significant and influential. The study aimed to determine the constructs in practice teaching experiences of technology livelihood and vocational education preservice teachers. To accomplish the goal of this study, quantitative research design, using exploratory factor analysis was applied. In addition to employing the Principal Component Analysis (CPA), exploratory factor analysis was also utilized to determine the factor structure of the measure and assess its internal reliability. Nine preservice teachers participated in the qualitative phase of the study, and 153 preservice teachers participated in the quantitative phase using purposive and stratified random sampling techniques. The study revealed the presence of the five components which are themed in factor loadings identified as Implementing Teaching Method, Observing Time Management, Costuming Self-Evaluation, Accepting Feedback, and Battling with Adversities with the Accepting Feedback having the lowest results. The themed factor loadings had a weighted overall mean score of 4.3285, which means that it was always observed. The researchers suggested that teacher education programs help pre-service teachers overcome obstacles they face when teaching, reflect on their practice, and solve problems to prepare them better to transition to in-service teaching. A confirmatory factor analysis is suggested to confirm the study's result under investigation.